JOINT WORK OF STEEL AND BASALT PLASTIC REINFORCEMENT WITH CONCRETE AS PART OF BEAM STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2021)
Experimental data on strength, deflections and cracking in beams are presented. Beams are made with dimensions 2000x200x100mm with steel and basalt-plastic (BFRP) reinforcement. They have been tested for static and low-cycle reloading. The results of studies of the main parameters of the performance of research elements are presented in the form of the corresponding experimental-statistical  dependences  for  the  actions  of  operational  and  destructive  loads  with  the  same  design factors. With the help of stochastic and graphical analysis, the influence of the type of reinforcement and design factors on the strength and deformation characteristics, as well as on the crack resistance of experimental samples - beams, is estimated.